2020
DOI: 10.1111/jphd.12432
|View full text |Cite
|
Sign up to set email alerts
|

Dental service utilization and immigrant family structure

Abstract: Objectives: To determine the patterns and time trends of dental services received and access to dental care among immigrant and US-born children living in the United States. Methods: We analyzed the nationally representative Medical Expenditure Survey data for 2007-2015. Survey weighted mean and frequency were calculated for all the years and for each year for the complete cohort and for the four subgroups of children categorized based on the child's and parents' birthplace (United States or Foreign). These gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Immigrant children's oral health is a growing dental public health concern. The oral health of immigrant populations is influenced by the factors of individuals, communities, and healthcare systems both before and after immigration, yet it remains unclear how these factors contribute to overall oral health disparities 31 . According to our findings, the participants residing in Istanbul, which is the most populated city in Turkey, had greater difficulties accessing dental care than the participants in the other cities.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Immigrant children's oral health is a growing dental public health concern. The oral health of immigrant populations is influenced by the factors of individuals, communities, and healthcare systems both before and after immigration, yet it remains unclear how these factors contribute to overall oral health disparities 31 . According to our findings, the participants residing in Istanbul, which is the most populated city in Turkey, had greater difficulties accessing dental care than the participants in the other cities.…”
Section: Discussionmentioning
confidence: 59%
“…Parental education programs and accessible preventive treatment are the most cost‐effective strategies to reduce the health burden on dental healthcare services. The continuous implementation of policies and programs that increase the access to and utilization of preventive dental services for immigrant populations was supported by the findings of previous research 31 …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Systems‐level approaches to providing preventive dental, vision, and mental health care to immigrant children are limited. Immigrant children are less likely to receive preventive dental care and more likely to have restorative and surgical care 68,90,91 . Immigrant children may also be identified as failing vision screens but may not have access to appropriate ophthalmologic follow‐up care 92 .…”
Section: Models Of Care Deliverymentioning
confidence: 99%
“…20 The measures used in this study have been reported to have high internal consistency and strong correlation in existing acculturation scales, such as language spoken at home and proportion of life lived in the United States. 20 Language reported has been found to be the strongest single predictor of acculturation, [21][22][23] followed by the proportion of life lived in the United States as an assessment of the level of exposure to US culture. 24 This study examined changes in acculturation level and socio-economic status and their association with preventive dental service use, receipt of restorative or surgical care and unmet dental needs.…”
Section: Introductionmentioning
confidence: 99%